LARVICIDAL EFFECTS OF KOREAN SEAWEED EXTRACTS ON BRINE SHRIMP ARTEMIA SALINA - Young Dae Kim; Jae-Suk Choi (Journal of Animal and Plant Sciences, 2017)
A total of 38 methanol and water extracts of macroalgal species (18 brown, 14 red, and 6 green) collected from the Korean coast were investigated for their lethality to brine shrimp larvae. Of the solutions tested, methanol extracts of six species (15.79%) showed larvicidal effects against Artemiasalina. Aqueous extracts of two species (5.26%) were lethal to A. salina. The brown algae Dictyotadichotoma, Eckloniakurome, Ishigeokamurae, Sargassumsagamianum, and Pachydictyoncoriaceum, and the green algae Enteromorphalinza and Ulvapertusa, displayed significant larvicidal activity in 2.5% methanol extracts. None of the methanol extracts of the 14 red algae species tested had larvicidal effects. The brown alga Colpomeniabullosaand the red alga Lomentariacatenata displayed significant larvicidal activity in 2.5% extracts. No larvicidal effects were observed from extracts of green algae. These results offer insight into the larvicidal potential of Korean seaweed extracts.
Keywords: Seaweed extract; Larvicidal effect; Artemiasalina; Enteromorphalinza; Gelidiumamansii